CommViz: Visualization of semantic patterns in large social communication networks. (January 2018) - Verspoor, Karin; Ofoghi, Bahadorreza; Robles Granda, Marlene
We introduce CommViz, an information visualization tool that enables complex communication networks to be explored, exposing trends and patterns in the data at a glance. We adapt a visualization approach known as hive plots to reflect the semantic structure of the networks, a generalization we call semantic hive plots . The method efficiently organizes and provides insight into complex, high-dimensional communication data such as email and messages on social media. We present the architecture of the CommViz tool and its application to the Enron email corpus as a case study, demonstrating how the structure of the visualization enables investigation of patterns and relationships in a large set of messages. We also provide a user study performed with Amazon Mechanical Turk that shows the value of the tool for certain complex data interrogations and further show how the incorporation of semantic structure on semantic coordinates can also be applied to parallel coordinates visualization. The integration of the social network characteristics with semantic attributes of the underlying data in a single visualization is, to our knowledge, a novel contribution of the work. The tool can be accessed athttp://commviz.eng.unimelb.edu.au . Code is available athttps://bitbucket.org/readbiomed/commviz . The Enron email corpus is available fromhttp://bailando.sims.berkeley.edu/enron_email.html .